The ultimate Peter Rabbit a visual guide to the world of Beatrix Potter - Hallinan, Camilla (New York : DK Pub., 2002)
Presents the life and work of Beatrix Potter through drawings, photographs, letters, journal entries, excerpts, and more.
Meet Peter Rabbit: Hello, Peter Rabbit -- How it all began -- A passion for pictures -- The original Peter Rabbit -- Off to the country -- The young storyteller -- The tale of Peter Rabbit -- The tale continues -- The tale is published -- A star is born -- Peter Rabbit's fan mail -- The Peter Rabbit doll -- Playtime with Peter -- More, please!: The tailor of Gloucester -- Waistcoats for mice -- Squirrel Nutkin -- The Lake District -- Peter Rabbit returns -- More about Mr. McGregor -- Two bad mice -- A new life for Beatrix -- Peter Rabbit's friends: Peter Rabbit's world -- Mrs. Tiggy-Winkle -- The pie and the patty-pan -- Come to tea -- Mr. Jeremy Fisher -- Tom Kitten -- Jemima Puddle-Duck -- Samuel Whiskers -- A funny old house -- Into the garden -- The Flopsy bunnies -- Mrs. Tittlemouse -- Ginger and Pickles -- Timmy Tiptoes -- Mr. Tod -- Over the hills and far away: Changing times -- Pigling bland -- A fierce bad rabbit & Miss Moppet -- Appley-Dapply & Cecily Parsley -- Johnny Town-Mouse -- Country life -- The fairy caravan -- Fairy feet & fleecy flocks -- Little Pig Robinson -- The last years -- Beatrix Potter's legacy -- Long live Peter Rabbit!: Follow that rabbit! -- Peter Rabbit goes global -- Peter Rabbit goes dancing -- Peter Rabbit on screen -- Peter Rabbit forever -- A Peter Rabbit map.
Includes index.
Keywords: Potter, Beatrix, -- 1866-1943; Potter, Beatrix, -- 1866-1943 -- Characters -- Peter Rabbit; Children's stories, English -- History and criticism; Authors, English -- 20th century; Artists -- Great Britain; Peter Rabbit (Fictitious character); Animals in literature; Animals in art; Authors, English; Women